2018
DOI: 10.5751/ace-01243-130206
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural destruction of Northern Pintail nests on cropland in prairie Canada

Abstract: ABSTRACT. It has been postulated that the decline of the Northern Pintail (Anas acuta) population is related to the propensity of female pintails to nest in cropland. Using spatial modeling at multiple scales, we estimated that the long-term average breeding population of Northern Pintails in prairie Canada would have initiated a mean of 974,260 nests/year, of which 47% (457,900 +/-43,270) would have been in cropland. Nest success rates are very low (5%) in spring-seeded cropland with predation and agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…9 M hectares of idled cropland (summer fallow) to continuous spring-seeded cropland under minimum tillage, has occurred over the past three decades 47,48 . The resultant increase in availability and use of spring-seeded versus idle cropland for nesting is the likely driver of declining reproduction levels 49,50 . At the observed level of annual funding for waterfowl habitat conservation ($31.3 M yr −1 ), it would take >100 years to cover the cost of habitat conversion ($35.7B) needed to achieve a predicted population size meeting the NAWMP goal of 4 M pintails.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 M hectares of idled cropland (summer fallow) to continuous spring-seeded cropland under minimum tillage, has occurred over the past three decades 47,48 . The resultant increase in availability and use of spring-seeded versus idle cropland for nesting is the likely driver of declining reproduction levels 49,50 . At the observed level of annual funding for waterfowl habitat conservation ($31.3 M yr −1 ), it would take >100 years to cover the cost of habitat conversion ($35.7B) needed to achieve a predicted population size meeting the NAWMP goal of 4 M pintails.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that productivity was negatively correlated with agricultural intensification at the subregional scale. Indeed a growing body of evidence from North America suggests that the decline in abundance of the pintail, a species that readily nests in residual crop stubble prior to seeding, may be linked to the increase in conservation tillage practices that reduce the availability of undisturbed stubble provided by fallowed cropland 49,50,108 . The economic value of birding and hunting associated with pintails in North America is estimated at >$100 M (2014 USD) annually 10 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations